2010
DOI: 10.1212/wnl.0b013e3181f11c1d
|View full text |Cite
|
Sign up to set email alerts
|

Regional patterns of brain tissue loss associated with depression in Parkinson disease

Abstract: Tissue loss in several WM regions within the cortical-limbic network occurs in PD-Dep vs PD-NDep patients. Such pattern of brain atrophy overlaps with key regions involved in major depressive disorders, suggesting an increased vulnerability of this neural circuit in PD. This may partially account for the high prevalence of depression in PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
101
2
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(112 citation statements)
references
References 30 publications
6
101
2
2
Order By: Relevance
“…A PET study found that PD patients with depression had decreased cerebral blood flow in the frontal cortex and in the anterior cingulate cortex when compared with PD patients without depression and controls [99]. Two VBM studies reported that depressed PD patients had lower grey matter density in the frontal, temporal cortex [92] (In this study patients had moderate disease stage, their average disease duration was 9.9 years and they were treated with Levodopa), in the posterior cingulate cortex and the hippocampus [94] (This study included patients with mild to moderate disease stages, average disease duration was 6 years and they were treated with Levodopa). Sheng et al [100] found that functional connectivity was decreased within the prefrontal-limbic system and increased in the prefrontal cortex and lingual gyrus in PD patients with depression.…”
Section: Depressionmentioning
confidence: 91%
See 3 more Smart Citations
“…A PET study found that PD patients with depression had decreased cerebral blood flow in the frontal cortex and in the anterior cingulate cortex when compared with PD patients without depression and controls [99]. Two VBM studies reported that depressed PD patients had lower grey matter density in the frontal, temporal cortex [92] (In this study patients had moderate disease stage, their average disease duration was 9.9 years and they were treated with Levodopa), in the posterior cingulate cortex and the hippocampus [94] (This study included patients with mild to moderate disease stages, average disease duration was 6 years and they were treated with Levodopa). Sheng et al [100] found that functional connectivity was decreased within the prefrontal-limbic system and increased in the prefrontal cortex and lingual gyrus in PD patients with depression.…”
Section: Depressionmentioning
confidence: 91%
“…These studies revealed that PD patients with depression had white matter reductions in the right anterior cingulate bundle, inferior orbitofrontal regions and in the left inferior parietal lobe [94], the frontal lobe bilaterally, possibly representing dysfunction in bilateral anterior cingulate bundles [96], and the mediodorsal nucleus of the thalamus bilaterally [95].…”
Section: Depressionmentioning
confidence: 96%
See 2 more Smart Citations
“…Of the 38 studies on depression, 33 reported findings from one single imaging modality: 19 used either PET [11, 12, 13,15, 16, 17, 18, 19] or SPECT 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 techniques, four used T1‐weighted imaging 31, 32, 33, three used DTI 34, 35, 36, six used resting state functional MRI (RS‐FMRI) 37, 38, 39, 40, 41, 42 and two used TCS methods 43, 44. The remaining four of the 38 studies reported findings from structural T1‐weighted imaging plus another imaging method, including PET 14, DTI 45, task FMRI 46 and RS‐FMRI 47, respectively.…”
Section: Methodsmentioning
confidence: 99%